Genetic abnormalities associated with acute lymphoblastic leukemia. Issue 6 (27th April 2016) - Yokota, Takafumi; Kanakura, Yuzuru
Abstract : Acute lymphoblastic leukemia (ALL) occurs with high frequency in childhood and is associated with high mortality in adults. Recent technical advances in next‐generation sequencing have shed light on genetic abnormalities in hematopoietic stem/progenitor cells as the precursor to ALL pathogenesis. Based on these genetic abnormalities, ALL is now being reclassified into newly identified subtypes. Philadelphia chromosome‐like B‐lineage ALL is one of the new high‐risk subtypes characterized by genetic alterations that activate various signaling pathways, including those involving cytokine receptors, tyrosine kinases, and epigenetic modifiers. Philadelphia chromosome‐like ALL is essentially heterogeneous; however, deletion mutations in the IKZF1 gene encoding the transcription factor IKAROS underlie many cases as a key factor inducing aggressive phenotypes and poor treatment responses. Whole‐genome sequencing studies of ALL patients and ethnically matched controls also identified inherited genetic variations in lymphoid neoplasm‐related genes, which are likely to increase ALL susceptibility. These findings are directly relevant to clinical hematology, and further studies on this aspect could contribute to accurate diagnosis, effective monitoring of residual disease, and patient‐oriented therapies. Abstract : Recent technical advances in next‐generation sequencing have shed light on genetic abnormalities in hematopoietic stem/progenitor cells as the precursor to pathogenesis of acute lymphoblastic leukemia. These findings are directly relevant to clinical hematology, and could contribute to accurate diagnosis, effective monitoring of residual disease, and patient‐oriented therapies.